Role of Organic Components in Electrocatalysis for Renewable Energy Storage. Issue 69 (19th November 2018) - Liu, Gejun; Bai, Haipeng; Zhang, Bo; Peng, Huisheng
Abstract: Carbon dioxide electroreduction and water splitting are known as two promising strategies to convert renewable intermittent electrical energy into chemical energy. Thus, the three half‐reactions, namely, CO2 reduction reaction, hydrogen evolution reaction, and the oxygen evolution counter reaction, in these two electrolytic processes have attracted wide research interest. Organic polymer electrocatalysts or electrocatalysts containing organic components play important roles in these catalytic processes. It has been shown that the organic molecules can efficiently catalyze the reactions themselves, and modulate the active sites towards high selectivity and efficiency. The roles of the organic molecules in conducting polymers, the metal complexes, and the framework materials are extracted for the three half‐reactions mentioned above, and this comprehensive review will serve as a guide for future research and aid in the design of electrocatalysts related to organic molecules. Abstract : Beyond metals : It has been shown that the organic molecules can efficiently catalyze electrocatalytic CO2 reduction, hydrogen evolution, and the oxygen evolution counter reaction. The roles of the organic molecules in conducting polymers, the metal complexes, and the framework materials are extracted for these three half‐reactions, and this comprehensive review will serve as a guide for future research and aid in the design of electrocatalysts related to organic molecules.